Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! To find the value of [tex]\(7x + 1\)[/tex] given the equation [tex]\(-2x - 1 = 7\)[/tex], we can follow these steps:
1. Solve for [tex]\(x\)[/tex] from the given equation:
The given equation is:
[tex]\[ -2x - 1 = 7 \][/tex]
To isolate [tex]\(x\)[/tex], first add 1 to both sides of the equation:
[tex]\[ -2x - 1 + 1 = 7 + 1 \][/tex]
Simplifying this, we get:
[tex]\[ -2x = 8 \][/tex]
Next, divide both sides by -2 to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{8}{-2} \][/tex]
This simplifies to:
[tex]\[ x = -4 \][/tex]
2. Substitute the value of [tex]\(x\)[/tex] into [tex]\(7x + 1\)[/tex] to find its value:
Now that we have [tex]\(x = -4\)[/tex], we substitute this value into [tex]\(7x + 1\)[/tex]:
[tex]\[ 7x + 1 = 7(-4) + 1 \][/tex]
Perform the multiplication:
[tex]\[ 7(-4) = -28 \][/tex]
Now add 1:
[tex]\[ -28 + 1 = -27 \][/tex]
Therefore, the value of [tex]\(7x + 1\)[/tex] is [tex]\(-27\)[/tex].
So, to summarize:
- The solution for [tex]\(x\)[/tex] from the equation [tex]\(-2x - 1 = 7\)[/tex] is [tex]\(x = -4\)[/tex].
- Substituting [tex]\(x = -4\)[/tex] into [tex]\(7x + 1\)[/tex] results in [tex]\(7 \cdot (-4) + 1 = -27\)[/tex].
Hence, the value of [tex]\(7x + 1\)[/tex] is [tex]\(-27\)[/tex].
1. Solve for [tex]\(x\)[/tex] from the given equation:
The given equation is:
[tex]\[ -2x - 1 = 7 \][/tex]
To isolate [tex]\(x\)[/tex], first add 1 to both sides of the equation:
[tex]\[ -2x - 1 + 1 = 7 + 1 \][/tex]
Simplifying this, we get:
[tex]\[ -2x = 8 \][/tex]
Next, divide both sides by -2 to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{8}{-2} \][/tex]
This simplifies to:
[tex]\[ x = -4 \][/tex]
2. Substitute the value of [tex]\(x\)[/tex] into [tex]\(7x + 1\)[/tex] to find its value:
Now that we have [tex]\(x = -4\)[/tex], we substitute this value into [tex]\(7x + 1\)[/tex]:
[tex]\[ 7x + 1 = 7(-4) + 1 \][/tex]
Perform the multiplication:
[tex]\[ 7(-4) = -28 \][/tex]
Now add 1:
[tex]\[ -28 + 1 = -27 \][/tex]
Therefore, the value of [tex]\(7x + 1\)[/tex] is [tex]\(-27\)[/tex].
So, to summarize:
- The solution for [tex]\(x\)[/tex] from the equation [tex]\(-2x - 1 = 7\)[/tex] is [tex]\(x = -4\)[/tex].
- Substituting [tex]\(x = -4\)[/tex] into [tex]\(7x + 1\)[/tex] results in [tex]\(7 \cdot (-4) + 1 = -27\)[/tex].
Hence, the value of [tex]\(7x + 1\)[/tex] is [tex]\(-27\)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.